Role of Calprotectin as a Modulator of the IL27-Mediated Proinflammatory Effect on Endothelial Cells - Susann A. Dorosz; Aurélien Ginolhac; Thilo Kähne; Michael Naumann; Thomas Sauter; Alexandre Salsmann; Jean-Luc Bueb (Mediators of Inflammation)
An underlying endothelial dysfunction plays a fundamental role in the pathogenesis of cardiovascular events and is the central feature of atherosclerosis. The protein-based communication between leukocytes and inflamed endothelial cells leading to diapedesis has been largely investigated and several key players such as IL6, TNFα, or the damage associated molecular pattern molecule (DAMP) calprotectin are now well identified. However, regarding cytokine IL27, the controversial current knowledge about its inflammatory role and the involved regulatory elements requires clarification. Therefore, we examined the inflammatory impact of IL27 on primary endothelial cells and the potentially modulatory effect of calprotectin on both transcriptome and proteome levels. A qPCR-based screening demonstrated high IL27-mediated gene expression of IL7, IL15, CXCL10, and CXCL11. Calprotectin time-dependent downregulatory effects were observed on IL27-induced IL15 and CXCL10 gene expression. A mass spectrometry-based approach of IL27 ± calprotectin cell stimulation enlightened a calprotectin modulatory role in the expression of 28 proteins, mostly involved in the mechanism of leukocyte transmigration. Furthermore, we showed evidence for STAT1 involvement in this process. Our findings provide new evidence about the IL27-dependent proinflammatory signaling which may be under the control of calprotectin and highlight the need for further investigations on molecules which might have antiatherosclerotic functions.